Randomised controlled trial of effects of Helicobacter pylori infection and its eradication on heartburn and gastro-oesophageal reflux: Bristol helicobacter project - Harvey, Richard F (BMJ Publishing Group Ltd., 2004)
Objectives To investigate the effects of Helicobacter pylori infection and its eradication on heartburn and gastro-oesophageal reflux. Design Cross sectional study, followed by a randomised placebo controlled trial. Setting Seven general practices in Bristol, England. Participants 10 537 people, aged 20-59 years, with and without H pylori infection (determined by the (13)C-urea breath test). Main outcome measures Prevalence of heartburn and gastro-oesophageal acid reflux at baseline and two years after treatment to eradicate H pylori infection. Results At baseline, H pylori infection was associated with increased prevalence of heartburn (odds ratio 1.14, 95% confidence interval 1.05 to 1.23) but not reflux (1.05, 0.97 to 1.14). In participants with H pylori infection, active treatment had no effect on the overall prevalence of heartburn (0.99, 0.88 to 1.12) or reflux (1.04, 0.91 to 1.19) and did not improve pre-existing symptoms of heartburn or reflux. Conclusions H pylori infection is associated with a slightly increased prevalence of heartburn but not reflux. Treatment to eradicate H pylori has no net benefit in patients with heartburn or gastro-oesophageal reflux.